Automatic pairing of real-world stimuli in younger and older adults: An event-related potential study - Petia Kojouharova; István Czigler; Boglárka Nagy; Zsófia Anna Gaál (PLoS ONE, 2026)
Contextual information can influence object perception, even when it is irrelevant to the task. When two unrelated stimuli frequently occur in close temporal succession, they may become associated. This process might be stronger in older adults due to age-related decline in inhibitory control, leading to deeper processing of irrelevant context. Automatic associations and their violations can be studied using visual mismatch negativity (vMMN), an event-related potential component reflecting the detection of violations of regularity in unattended stimuli. In our study, younger ( n = 18, M = 21.2 ± 2.1 yrs) and older ( n = 17, M = 69.8 ± 2.8 yrs) adults viewed pairs of images presented in succession: a scene (forest or street) followed by an emotional face (happy or angry). One scene–emotional face combination occurred frequently, the other rarely, forming a contextual oddball sequence. All individual stimuli appeared equally often. Participants performed an unrelated colour-change detection task, ensuring that the scene–emotional face pairs were unattended. We expected a vMMN to the emotional face in rare pairings, especially in older adults if they formed stronger associations. A control oddball condition with only emotional faces verified automatic emotion discrimination. In the control condition, vMMN emerged for both deviant emotions (in various ranges within the 94–276 ms post-stimulus time window). However, no vMMN was observed in the scene-emotional face pair condition. Instead, younger adults showed an early posterior positivity (90–161 ms) to rare pairings, while older adults exhibited a later negativity (356–384 ms). These results suggest that task-irrelevant, thematically unrelated visual events can become associated through temporal proximity. However, violations of these associations evoke neural responses distinct from vMMN and vary across age groups, with older adults relying on later, potentially semantic-related mechanisms rather than early visual processes to detect the regularity.